Nurses’ Perceptions of Critical Issues Requiring Consideration in the Development of Guidelines for Professional Registered Nurse Staffing for Perinatal Units - Simpson, Kathleen Rice (2012)
OBJECTIVE: To solicit input from registered nurse members of the Association of Women’s Health, Obstetric and Neonatal Nurses (AWHONN) on critical considerations for review and revision of existing nurse staffing guidelines. DESIGN: Thematic analysis of responses to a cross-sectional on-line survey question: “Please give the staffing task force your input on what they should consider in the development of recommendations for staffing of perinatal units.” PARTICIPANTS: N = 884 AWHONN members. MAIN OUTCOME MEASURE: Descriptions of staffing concerns that should be considered when evaluating and revising existing perinatal nurse staffing guidelines. RESULTS: Consistent themes identified included the need for revision of nurse staffing guidelines due to requirements for safe care, increases in patient acuity and complexity, invisibility of the fetus and newborn as separate and distinct patients, difficulties in providing comprehensive care during labor and for mother-baby couplets under current conditions, challenges in staffing small volume units, and the negative effect of inadequate staffing on nurse satisfaction and retention. CONCLUSION: Participants overwhelmingly indicated current nurse staffing guidelines were inadequate to meet the needs of contemporary perinatal clinical practice and required revision based on significant changes that had occurred since 1983 when the original staffing guidelines were published.